Optimalisasi Kader dalam Upaya Mendukung Proses Persalinan Aman dan Nyaman Melalu Pelatihan Penggunaan Lembar Balik - Irianti, Bayu; Astriyani, Endang (Jurnal Pengabdian kepada Masyarakat (ABDIKEMAS), 2025)
Childbirth is a short process that is critical and requires cooperation between partners and health workers. Knowledge about childbirth preparation and the delivery process is important for every childbirth partner to understand, as an effort to increase comfort and safety during childbirth. Health cadres in selected communities are elected voluntarily to help improve health and are trained to mobilize the community to participate in community empowerment in the health sector. The purpose of community service activities is to optimize the role of cadres in a safe and comfortable childbirth process as a strengthening of the Primary Service Transformation pillar in the work area of the Tamansari Health Center. The method includes three stages: preparation, implementation, and evaluation. The implementation used assessments before and after the training on using flip sheets for 28 cadres, and observation of the process, to see the activeness and ease of using flip sheets. The results were obtained in that an increase in knowledge before and after the training to cadres with an increase in average knowledge about nutrition by 1.75 knowledge about pain reduction by 1.54, and an increase in average perception by 1.10 (ρ<0.05). Health cadres have a role in improving public health, empowering and optimizing the role of health cadres through training on the use of safe and comfortable childbirth flip sheets can increase cadre knowledge and make it easier for cadres to convey information to the public, and the use of promotional media is important to support labor of information properly.